The Main Sources of Research on Ethnopedagogics of Crimean Tatars - Zarema Asanova (Pedagogical Discourse, 2013)
The article identifies the main sources of research on ethnopedagogics of Crimean Tatar people. The author picks out the source-books such as: 1 ) scientific work of ethnopedagogics of Crimean Tatars, 2) the collections of the Crimean Tatar folklore, 3) works of ancient writers and thinkers, scientists and lexicographer of the East, religious thinkers of the Muslim world and the Muslim holy book – the Koran, 4) literary works of the Crimean Tatar poets and writers, 5) research notes government officials, anthropologists, travelers, historians, linguists and cultural studies on the culture of the Crimean Tatars, 6) the works of the classical teachers of popular education, 7) modern ethnopedagogical, educational and psychological research.